2016
DOI: 10.1101/090399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MtrA is an essential regulator that coordinates antibiotic production and sporulation inStreptomycesspecies

Abstract: Streptomyces bacteria make numerous secondary metabolites, including half of all 25 known antibiotics. Production is coordinated with their complex life cycles but the regulators 26 that coordinate development with antibiotic biosynthesis are largely unknown. This is 27 important to understand because most Streptomyces secondary metabolites are not produced 28 under laboratory conditions and unlocking the 'cryptic' biosynthetic gene clusters (BGCs) is a 29 major focus for antibiotic discovery. Here we characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…The fact we could delete mtrA in a strain carrying this construct suggested that MtrA-3xFlag is functional and the strain grew like the wild-type (Supplementary Figure S2 ). We performed ChIP-seq on cultures grown for 8, 10, 12, 14, 16, 18, and 20 h in liquid MYM medium (NCBI Geo database accession number GSE84311 ; Figure 1 ; Som et al, 2016 ). Reads were mapped to the S. venezuelae NRRL B-65442 genome (GenBank accession number CP018074 ) and the chloramphenicol BGC was examined for MtrA ChIP peaks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact we could delete mtrA in a strain carrying this construct suggested that MtrA-3xFlag is functional and the strain grew like the wild-type (Supplementary Figure S2 ). We performed ChIP-seq on cultures grown for 8, 10, 12, 14, 16, 18, and 20 h in liquid MYM medium (NCBI Geo database accession number GSE84311 ; Figure 1 ; Som et al, 2016 ). Reads were mapped to the S. venezuelae NRRL B-65442 genome (GenBank accession number CP018074 ) and the chloramphenicol BGC was examined for MtrA ChIP peaks.…”
Section: Resultsmentioning
confidence: 99%
“…A preprint covering this work is available at bioRxiv: Som et al (2016). We thank David Jakeman (Dalhousie University, Canada) for an authentic jadomycin A standard.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This research was supported by a BBSRC PhD studentship to N. S., a UEA-funded PhD studentship to F. K., a Medical Research Council grant G0801721 to M. I. H. and Natural Environment Research Council responsive mode grants NE/M015033/1 and NE/M014657/1 to M. I. H. and B. W. An earlier version of this work was published as a preprint on bioRxiv [ 31 ].…”
Section: Funding Informationmentioning
confidence: 99%
“…In addition, several Streptomyces strains, such as Streptomyces hygroscopicus, Streptomyces malaysiensis, Streptomyces violaceusniger YH27A, S. coelicolor, S. violaceusniger YCED-9, and Streptomyces sp. isolate KY-33, isolated from rhizosphere soil, have been reported to be potential antifungal agents against different soil-borne plant pathogens (Cheng et al, 2010;Gherbawy et al, 2012;Wu et al, 2012;Ghadge and Patil, 2016;Som et al, 2017;Shrivastava and Kumar, 2018). The P-solubilizing Streptomyces griseus BH7 strain, isolated from Moroccan phosphate mines, was shown to inhibit the growth of potentially phytopathogenic fungi, bacteria (gram+/-) and yeasts.…”
Section: Phosphate-solubilizing Streptomyces As Biocontrol Agentsmentioning
confidence: 99%